Efektifitas Metode Restorative Justice Terhadap Penyelesaian Perkara Pidana Di Polsek Waesala Kabupaten Seram Bagian Barat - Aindo, La Ode; Mbunai, La Ode (JUSTLAW : Journal Science and Theory of law, 2025)
This research is an Empirical Legal Research. Empirical Legal Research is a type of legal research in which empirical law (empirical legal research), a study conducted by collecting field data sourced from interviewed sources and based on numerical data that has been collected by related institutions. In this study, the author uses a normative and empirical approach in qualitative research literature and field studies this time. The author will combine legal elements and support them with field data. This study found that the Concept of Restorative Justice in Indonesia conceptually has several legal regulations governing it, starting from the 1945 Constitution, Supreme Court Regulations, Regulations of the Indonesian Attorney General's Office and Regulations of the Chief of Police. All of these regulations have provided instructions on how Restorative Justice is implemented and what criminal acts can be resolved using the Restorative Justice method. The effectiveness of the Restorative Justice method in resolving criminal cases at the Waesala Police Station, West Seram Regency has not been running well. This is certainly caused by the mindset of the community who do not understand Restorative Justice as a method for resolving criminal cases. In addition to the mindset of the community, the ineffectiveness of Restorative Justice in resolving criminal cases at the Waesala Police Station, West Seram Regency is caused by the types of cases that can be resolved.